From culture to ideology in comparative politics: (a review article) - Hanson, Stephen E. (2003)
Four recent books focus on the importance of the subjective orientations of social actors in empirical political outcomes, but they attempt to overcome the methodological and conceptual problems of research in the culturalist tradition in different ways. There has been a move toward greater specificity in defining the particular kinds of belief systems that can serve as independent variables. This welcome trend indicates the importance of distinguishing more clearly between ideologies - formal, explicit, relatively consistent definitions of political community articulated by political elites - and cultures - informal, implicit, relatively inconsistent understandings of political community held by people within a given institutional setting. - Reproduced.
Keywords: Politics and government